Product Sales Analysis in the Marketing Management Process at PT. Ajinomoto Indonesia - Seppa, Yusi Irensi; Baharuddin, Aris; Zainal, Nur Hikmah (Pinisi Business Administration Review, 2025)
Product sales are one of the indicators in the marketing management process where in a competitive economic era like today, business processes will not succeed if the company is not able to implement the right marketing management process. This research aims to be able to find out more deeply related to product sales analysis in the marketing management process at PT. Ajinomoto Indonesia. The type of research used is a qualitative descriptive approach that can help researchers by explaining the realities in the field. Data collection techniques are in the form of observations, interviews, field notes and documentation. Data analysis techniques are in the form of data collection with interpretation, data condensation, data display (data presentation), and drawing conclusions. The results of the study show that product sales consist of creating, selling, advertising/promotion, distributing and serving in a marketing management process at PT. Ajinomo Indonesia is done in various ways. PT. Ajinomoto Indonesia carries out the stage of creating/designing products in sales analysis, one of which is through planning and scheduling production, also starting with the process of sorting raw materials after which it enters the production stage and after the finished product, the product must go through a process of checking the feasibility of consumption. PT. Ajinomoto Indonesia carries out the stage of selling its products in conventional ways and through e-commerce. PT Ajinomoto Indonesia uses non-personal forms of advertising including advertising in print, television, radio, and digital/social media. Sales promotion at PT. Ajinomoto Indonesia is carried out by providing short-term incentives to encourage consumers to try or buy and sustainability principles. Delivery products carried out by PT. Ajinomoto Indonesia Mojokerto Factory is divided into two, namely domestic and export. PT Ajinomoto Indonesia offers a variety of product sales services that aim to meet consumer needs and increase customer satisfaction. Some aspects of the sales services provided include product support, customer service, marketing/promotion, ease of purchase, training or education, and also product innovation.